A CHOIR INTERVENTION TO PROMOTE WELL-BEING AMONG DIVERSE OLDER ADULTS: THE COMMUNITY OF VOICES TRIAL. (11th November 2018) - Johnson, J; Stewart, A; Anna, N; Acree, M; Flatt, J; Max, W; Gregorich, S
Abstract: Objectives: To report intention-to-treat results of a pragmatic, cluster-randomized trial to examine the effect of Community of Voices, a multi-modal community choir intervention, on the health and well-being of racial/ethnically and socioeconomically diverse older adults. Method: Twelve Administration-on-Aging-supported senior centers were randomized to receive the choir intervention immediately or after a six-month delay. We recruited community-dwelling adults aged 60 and over. The choir intervention was culturally tailored around three engagement components (cognitive, physical, and psychosocial) and delivered at senior centers by community-based music professionals. The main randomized comparison was at 6 months (after 23 choir sessions). Results: The sample (N=390) had a mean age of 71.3 (SD=7.2); 65% were from non-white racial/ethnic backgrounds. Study retention was 92%. Intention-to-treat analyses found a significant group-by-time interaction effect for two of six psychosocial outcomes: participants in the choir intervention experienced significant improvements in loneliness and interest in life compared to the wait-list controls. No significant group differences were observed for cognitive or physical outcomes. Discussion: The finding that singing in a choir can reduce loneliness and increase interest in life in diverse older adults are important because of the relatively low-cost and cultural salience of the intervention. This supports further efforts to examine how engagement in the arts may improve health and well-being and reduce health disparities in diverse older adults.